2018
DOI: 10.1080/22423982.2018.1498681
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic characteristics, sexual behaviour and knowledge about cervical cancer prevention as risk factors for high-risk human papillomavirus infection in Arkhangelsk, North-West Russia

Abstract: While sociodemographic predictors of cervical cancer (CC) are well understood, predictors of high-risk (HR) human papillomavirus (HPV) infection have not been fully elucidated. This study explored the HR-HPV infection positivity in relation to sociodemographic, sexual behavior characteristics and knowledge about HPV and CC prevention among women who visited the Arkhangelsk clinical maternity hospital named after Samoylova, Russia. This cross-sectional study was conducted in the city of Arkhangelsk, Northwest R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
2
4
0
1
Order By: Relevance
“…Younger women had an HPV infection most frequently. Our data correspond to the results of other studies, according to which the peak of HPV detection occurs in age groups of women younger than 30 years old who have the highest sexual activity and change of sexual partners (Zeng et al, 2016;Roik et al, 2018). In the United States population, the prevalence range of HPV positive was in young women under 30 years old, between 41-51% (Karuri et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Younger women had an HPV infection most frequently. Our data correspond to the results of other studies, according to which the peak of HPV detection occurs in age groups of women younger than 30 years old who have the highest sexual activity and change of sexual partners (Zeng et al, 2016;Roik et al, 2018). In the United States population, the prevalence range of HPV positive was in young women under 30 years old, between 41-51% (Karuri et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…No fixed pattern of the HPV genotypes distribution observed even in different parts of a province, e,g, the samples from suburb of Tehran commonly demonstrated mixed infections (the data were not shown). Although no sociodemographic data are available, low education and inappropriate economic conditions may be an explanation, high risk HPV distribution is affected by sexual behavior, host immune factors, environmental factors, smoking, having multiple sex partners, and the presence of other sexually transmitted infections (16). Therefore, HPV as an important transmitted infection causes some critical HPV-associated cancers in human, circulating HPV genotypes should be available to plan better the prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of cervical cancer are caused by HPV infection ( 48 ). Although surgical treatment, chemotherapy and radiotherapy have a therapeutic effect on cervical cancer, this effect is insufficient ( 49 ). Recent studies have reported that lncRNAs play important regulatory roles in cervical cancer ( 50 52 ).…”
Section: Discussionmentioning
confidence: 99%